Global Development of International Tourism and Impact on the Economy of Ukraine - Moskvichova, Olena; Hryhoruk, Iryna; Marchenko, Yuliia; Veretilnyk, Yuliia (European Journal of Sustainable Development, 2021)
The article highlights the geopolitical aspects of the international tourism development in Ukraine as a global phenomenon that carries out economic, social and international and political action. In today's world, tourism has become a powerful industry, a huge complex in which the economic and social spheres are connected. The importance of tourism in international economic activity is constantly growing, and the market itself is acquiring new trends and features, affecting trade, transport and communications, agriculture and construction. The processes of globalization in the tourism market are characterized by changes in technology, modernization of transport infrastructure, internationalization of business activity and the creation of a regulatory mechanism. The potential of world tourist flows as factors of geopolitical influence is revealed, the structure of which reflects and influences the tendencies of international interaction. The main geopolitical factors influencing the dynamics and spatial organization of international tourist flows are structured. The world market of tourist services has a clear segmentation character. The main criteria for segmentation are motivational, age and regional ones. The general tendencies of development of the international tourism, a role and a place of Ukraine in the international tourist market are characterized. It is predicted that China will become the most popular tourist country in the near future. It is determined that due to the growth of intercontinental ties, which is based on the rapid development of vehicles and, above all, jet aircraft, as well as the desire of a significant number of people to visit the most remote and exotic corners of the Earth, tourism exchange between regions will develop more intensively than within regions. However, there is a growing tendency to increase the exchange of tourists between neighboring countries under conditions of normal relations between them and between countries with related languages. The main world events that have affected tourist flows in recent years are listed: Brexit, COVID-19, military actions in Eastern Ukraine and others. The analysis of international tourist flows in Ukraine was done, in particular their dynamics and spatial structure during 2010-2019 in the context of military-political aggression by Russia and the aggravation of Ukrainian-Russian interstate relations. It is established that the current dynamics of the international tourist flow in Ukraine is characterized by a sharp decrease in international visitors, slowing down the development of tourism and reformatting the spatial structure of the incoming and outgoing tourist flow. It is also noted that among the main factors hindering the development of the Ukrainian tourism industry are the unsatisfactory state of development of infrastructure and logistics of tourism, high prices, environmental and criminal risks, low innovation activity of tourism enterprises. It is concluded that international tourism is not only a passive participant in international relations, but also an active political actor who is able to act as a channel for establishing international trust and cooperation, a factor in maintaining political stability.